Microbiological properties and volatile compounds of salted-dried goose - Kaya, Mükerrem; Börekçi, B. Sayın; Hazar, F. Y.; Kızılkaya, P.; Kabil, E.; Kaban, Güzin (Elsevier BV, 2020)
Salted-dried goose is a traditional Turkish product with specific flavor that is produced by dry salting, post-salting, and subsequently air-drying of the goose carcass. In this study, the leg and breast parts of salted-dried goose carcasses were analyzed in terms of microbiological properties and volatile compounds. Lactic acid bacteria and Micrococcus-Staphylococcus bacteria constituted a significant part of microbiota in both leg and breast samples. The Enterobacteriaceae count was below the detectable level (<2 log cfu g-1) in 60% of the leg samples and in 47% of the breast samples. The yeast-mold count was less than 5 log cfu g-1 in 80% of both leg and breast samples. Many volatile compounds belonging to different chemical groups, including aldehydes, aliphatic and aromatic hydrocarbons, esters, alcohols, terpenes, ketones, sulfur compounds, and furans, were identified from samples. The breast samples showed a higher mean amount of hexanal than the leg samples. No significant difference was found between the breast and leg samples in terms of ketones and sulfur compounds. It was also determined that a considerable part of volatile compounds is formed by lipid oxidation.
Keywords: Volatile Organic Compounds; Meat; Turkey; Food Handling; goose meat; Processing and Products; Goose Meat; SF1-1100; Animal culture; lactic acid bacteria; Lactic Acid Bacteria; Enterobacteriaceae; hexanal; Geese; Animals; Salts; Desiccation; volatile compound; Hexanal; Volatile Compound; 2. Zero hunger; 3. Good health